Suppression of Impedimetric Baseline Drift for Stable Biosensing. (1st September 2022) - Gezahagne, Hilena F.; Brightbill, Eleanor L.; Jin, Decarle S.; Krishnathas, Siamalan; Brown, Billyde; Mooney, Mark H.; O'Riordan, Alan; Creedon, Niamh; Robinson, Caoimhe; Vogel, Eric M.
Abstract : Biosensors based on Electrochemical Impedance Spectroscopy (EIS) detect the binding of an analyte to a receptor functionalized electrode by measuring the subsequent change in the extracted charge-transfer resistance (RCT ). In this work, the stability of a long chain alkanethiol, 16-mercaptohexadecanoic acid was compared to that of a polymer-based surface linker, ortho-aminobenzoic acid (o-ABA). These two classes of surface linkers were selected due to the marked differences in their structural properties. The drift in RCT observed for the native SAM functionalized gold electrodes was observed to correlate to the drift in the subsequent receptor functionalized SAM. This indicates the importance of the gold-molecule interface for reliable biosensing. Additionally, the magnitude of the baseline drift correlated to the percentage of thiol molecules improperly bound to the gold electrode as evaluated using X-ray Photoelectron Spectroscopy (XPS). Alternatively, the o-ABA functionalized gold electrodes demonstrated negligible drift in the RCT . Furthermore, these polymer functionalized gold electrodes do not require a stabilization period in the buffer solution prior to receptor functionalization. This work emphasizes the importance of understanding and leveraging the structural properties of various classes of surface linkers to ensure the stability of impedimetric measurements.